Instream Flow Rights for Protecting River Ecology in Nigeria's Bitumen Zone: Learning From Uganda's Experience - Akinsulore, Adedoyin Olusegun; Adejumo, Oluwadamilola Adebola; Aidonojie, Paul Atagamen (Universitas Muhammadiyah Tangerang, 2024)
Water is a vital resource essential for the survival of humans, animals, and ecosystems. Its inclusion in the Sustainable Development Goals (SDGs) underscores its importance. Effective management and regulation of water resources are critical for achieving development across key sectors. However, freshwater scarcity is an increasing concern, particularly with the high water consumption involved in bitumen mining and production. This study employs a hybrid research method to assess water resource regulation in Nigeria and Uganda. A total of 226 questionnaires were distributed to respondents in Nigeria, and the data was analyzed using descriptive and analytical techniques. The findings reveal a lack of a robust legal framework regulating water usage in bitumen mining in Nigeria, in contrast to Uganda, where more comprehensive water regulations exist. The study further concludes that unregulated water withdrawals for bitumen production in Nigeria threaten the achievement of SDG 6.4, which focuses on sustainable water use. To prevent ecological disasters and ensure the sustainability of freshwater ecosystems in Nigeria's bitumen belt, the study recommends strengthening existing legal and institutional frameworks to guarantee instream flow and sustainable water use in mining activities, drawing from the experiences of countries like Uganda.Keywords: Bitumen, Freshwater, Instream Flow, Mining, Sustainable Development Goals, Water Management